Keterangan Pelatihan Pembukuan, Pencatatan Dan Pelaporan Keuangan Sederhana Menuju Entrepreneur Modern, Inovatif Dan Unggul Kepada Karang Taruna - Januar Eky Pambudi; Hendra Galuh Febrianto; Indra Gunawan Siregar; Basuki Basuki; Mikrad Mikrad; Priyo Susilo (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
Karang Taruna as a social organization as well as a forum and means for the development of every member of society which grows and develops on the basis of social awareness and responsibility from, by and for the community, especially the young generation in the village/sub-district area, is primarily engaged in the field of social welfare business." Karang Taruna Pasir Jaya is still under the auspices of the Village, so it receives funding every year from the Village government. Therefore, competent Human Resources (HR) are needed to produce quality financial reports. Through this community service activity, it is hoped that the community, especially youth organizations, will understand the concept and meaning of the Cash Book, namely a financial journal containing records of cash receipts and payments, as well as understand the benefits of the Cash Book. This activity is carried out through outreach, training and mentoring to members of the Pasir Jaya Youth Organization. Based on the Community Service activities that have been carried out, there were participants who were able to understand 75% of the material. The result of this service activity is to increase the knowledge of the community, especially youth organizations, about the bookkeeping system, recording daily transactions so that the business carried out can provide the expected profits.